2019
DOI: 10.29138/prd.v1i2.148
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Celebrity Endorser, Product Quality and Price on Purchase Decisions and Customer Satisfaction on Vivo Brand Smartphones in Surabaya

Abstract: Smartphone is a virtual communication tool in two directions that makes easy for individuals to interact through short message, telephone and an internet network. The purpose of this study was to analyze the influence of celebrity endorser, product quality and price on purchasing decisions and customer satisfaction. This research used quantitative methode with population 100 respondents who use Vivo brand smartphones in Surabaya. The analysis used partial least square, data obtained from questionnaires and tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…There are several indicators used in this study, including attractiveness, trustworthiness, expertise, and similarity taken from Ifeanyichukwu (2016), as well as imperatives taken from research Lk et al (2019). Based on the several definitions mentioned above, it can be concluded that the celebrity endorser it is expected can strengthen the impression of the product in the minds of consumers regarding the message or information that will be conveyed so that later it will bring up consumer behavior, namely making purchasing decisions for a product.…”
Section: Celebrity Endorsermentioning
confidence: 99%
“…There are several indicators used in this study, including attractiveness, trustworthiness, expertise, and similarity taken from Ifeanyichukwu (2016), as well as imperatives taken from research Lk et al (2019). Based on the several definitions mentioned above, it can be concluded that the celebrity endorser it is expected can strengthen the impression of the product in the minds of consumers regarding the message or information that will be conveyed so that later it will bring up consumer behavior, namely making purchasing decisions for a product.…”
Section: Celebrity Endorsermentioning
confidence: 99%